Biomarkers in Skin Mucus for a Minimally Invasive Approach to Stress in Red Tilapia (Oreochromis sp.) Fry - Hernán Antonio Alzate-Díaz; Laura Fernández-Alacid; Sandra Clemencia Pardo-Carrasco (Biology)
In a context where aquaculture continues to grow, it is essential to understand how culture conditions influence fish stress. The welfare of red tilapia fry (Oreochromis sp.), weighing 0.6 ± 0.3 g and with an initial total length of 3.548 ± 0.285 cm, was evaluated in two culture systems, biofloc and land-based ponds, over a period of 30 days through biomarkers associated with the skin mucosa, such as protein, glucose, lactate, and the hormone cortisol, in addition to their relationships with protein, seeking a comprehensive view of the physiological state and stress of these fish. Mucus samples were thawed and prepared by mechanical homogenization and centrifugation. The results reveal that the biofloc system provides a more conducive environment for welfare, evidenced by higher mucus protein levels of 1.598 ± 0.733 mg/mL, 2.316 ± 1.01 mg/mL, and 1.203 ± 0.640 mg/mL for culture days 10, 20 and 30, respectively, and lower cortisol > 1 ng/mL and lactate contents 1799 ± 1135 µg/mL, 30,271 ± 24,613 µg/mL, and 21,829 ± 23,507 µg/mL for culture days 10, 20 and 30, respectively, compounds largely associated with animal stress. This highlights the direct relationship between culture, environment and fish health and highlights skin mucus as a valuable minimally invasive biomarker. It is also important to note that improved fish welfare supports fish growth and health and promotes more sustainable aquaculture practices, contributing to more efficient and responsible production in the industry.